2011
DOI: 10.1177/1010539511402053
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Freedom to Lead a Life We Have Reason to Value? A Spotlight on Health Inequity in the Asia Pacific Region

Abstract: The Asia Pacific region is home to more than 60% of the world's population. Life expectancy at birth differs between countries by as much as 27 years. This article suggests that asymmetric economic growth, unplanned urbanization, marked environmental change, unequal improvements in daily living conditions, and the unequal distribution and access to quality health care have contributed to health inequities in the Asia Pacific region. Contextually specific evidence and action are needed. This requires ongoing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Infrastructural improvements and the growth of the middle class are driving the expansion and improvement of the health system and reducing geographical and economic barriers to health care, particularly for urban and non-poor rural residents. 28,29 Nonetheless, our findings show that some vulnerable groups are being left behind and that the equity gap is widening. Conditions in Viet Nam differ from those that exist in nearby countries.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Infrastructural improvements and the growth of the middle class are driving the expansion and improvement of the health system and reducing geographical and economic barriers to health care, particularly for urban and non-poor rural residents. 28,29 Nonetheless, our findings show that some vulnerable groups are being left behind and that the equity gap is widening. Conditions in Viet Nam differ from those that exist in nearby countries.…”
Section: Discussionmentioning
confidence: 62%
“…The causes and determinants of these inequities are manifold and diverse, as has been shown in several studies. 29,34,35 Informal payments and a growing private sector, together with weak public health insurance, generate inequities because people's ability to pay for services parallels the increasing income divide in society. 34 Additionally, modernization has generated greater social complexity, with fewer opportunities for the less educated in society.…”
Section: Discussionmentioning
confidence: 99%
“…In a broad literature review on health inequity in Asia, Friel et al [22] stressed that the health of people in Asia is shaped by both socioe-conomic and environmental conditions, as well as persistent health inequities. They found that a lack of clean drinking water was a strong indicator of health inequity in Asia.…”
Section: Resultsmentioning
confidence: 99%
“…In order to reduce inequities, it is vital that high quality, locally derived, and disaggregated data become available to inform the development, implementation, and evaluation of SDH policies and interventions and that local research cadres are available to provide this data. Research on the socio-economic drivers of health inequity is an emerging field worldwide [12–14], and there was a needed for better training possibilities for SDH research, particularly in LMICs [2, 15]. In response to this need the INTREC (INDEPTH Training & Research Centres of Excellence) collaboration developed and piloted a training programme on SDH research for health- and demographic researchers in LMIC’s in Africa and Asia.…”
Section: Introductionmentioning
confidence: 99%